2005
DOI: 10.3736/jcim20050309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perioperative administration of rhubarb on acute inflammatory response in patients with gastric cancer

Abstract: Rhubarb can positively modulate the acute inflammatory response, promote the recovery of postoperative gastrointestinal motility, and benefit enteral nutrition support in patients who have undergone major operations for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…MXD is a modified version of XD, with the addition of three components: Astragalus, Frankincense, and Myrrh on the basis of XD. Rhubarb[ 50 - 53 ], Astragalus[ 54 - 58 ], and Magnolia officinalis[ 59 - 61 ] have immune protection effects and reduce the inflammatory stress response. MXD may improve the recovery of GI function of patients with cholelithiasis in the perioperative period under ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…MXD is a modified version of XD, with the addition of three components: Astragalus, Frankincense, and Myrrh on the basis of XD. Rhubarb[ 50 - 53 ], Astragalus[ 54 - 58 ], and Magnolia officinalis[ 59 - 61 ] have immune protection effects and reduce the inflammatory stress response. MXD may improve the recovery of GI function of patients with cholelithiasis in the perioperative period under ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin (1,3,8-trihydroxy-6-methylanthraquinone) has been reported to suppress the growth of tumor in some clinical situations (Cai et al, 2005;Mantani et al, 2002) and effectively inhibit tumor metastasis in vitro and in vivo Huang et al, 2006). Some studies investigated the effects and mechanisms of emodin on cell death in human prostate, lung, liver, and cervical, and blood cancer cells (Cha et al, 2005;Chen et al, 2002;Fu et al, 2007;Jing et al, 2002;Jing et al, 2006;Lee, 2001;Muto et al, 2007;Su et al, 2005;Yi et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…It has the effects of purgation, purging heat, loosening the bowels, curing metal and renal disorders and removing bacterial dysentery (Kang et al, 2006;Wang et al, 2007;Yue, 1990). Recent studies found that rhubarb has the action of antitumor and antimutagenicity (Cai et al, 2005, Kang et al, 2006Sun et al, 2000). Anthraquinones and bianthrones, including emodin and rhein were considered in the last decades as a cancer chemopreventative agent and therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It is known to exert several biological effects, which involve purgative, antipyretic, anti-inflammatory, anti-angiogenic, and antineoplastic activities [ 13 15 ]. The previous study reported that the administration of rhubarb modulated acute inflammatory response in patients with gastric cancer [ 16 ]. Furthermore, we previously reported the increase in free radical scavenging activities of Rhei Rhizoma and Glycyrrhiza Rhizoma combined extract (RGE) in the inflammation induced ROS [ 17 ].…”
Section: Introductionmentioning
confidence: 99%